Mindfulness and decision-making for teachers—the mediating role of self-esteem and the moderating role of experience - Almohammadi, Afaf S. (Frontiers in Education, 2025)
ObjectivesThis study aimed to determine the relationship between mindfulness, self-esteem, and decision-making. The study focused to examine the relationship primarily between mindfulness and decision-making, with self-esteem as a mediator and experience as a moderator among teachers in Saudi Arabia.MethodsA survey was conducted among teachers in Saudi Arabia and was completed by 525 teachers (67.8% were females and 32.2% were males, with an average age of 38.25 years, standard deviation [SD] = 8.72). Participants were Arabic-speaking teachers who were selected from public and private schools in Saudi Arabia. They were selected via direct contact with schools in Riyadh. Using the snowball spreading techniques, the teachers were recruited from elementary, middle, and high schools. Adolescent and Adult Mindfulness Scale (AAMS), Rosenberg Self-Esteem Scale (RSES), and Decision-Making Scale were used to obtain information on the variables.ResultsMindfulness was significantly and positively correlated with decision-making and positive self-esteem and negatively correlated with negative self-esteem. Decision-making was significantly positively correlated with positive self-esteem and negatively correlated with negative self-esteem. Moreover, positive self-esteem partially mediated the relationship between mindfulness and decision-making, indirectly. However, mindfulness was not predicted by decision-making through negative self-esteem. A multigroup analysis showed that the mediational model was moderated by high teaching experience.ConclusionThe results prove that mindfulness and self-esteem are associated with decision-making. Self-esteem and mindfulness for teachers increase their awareness of the problems they face daily in the classroom. Additionally, more experienced teachers are more confident and portray better decision-making skills.